2006
DOI: 10.1016/j.rapm.2006.06.251
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epithelial Cell Transfer in Spinal Areas by Light Microscopy and Determining Any Tissue Coring via Cell Culture During Combined Spinal-Epidural Interventions

Abstract: We could not reproduce the cells or cell debris obtained during the CSE interventions in vivo, which can be explained by a possible structural deformation of cells or the inadequacy of the amount of cells that were transferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In accordance with our previous studies and other recently published data [6,8,9], our study failed to demonstrate transportation of stratum basale cells, which, with their proliferative potential, could produce an epidermal tumour. Only stratum corneum cells ready to desquamate from the outermost layers of the skin could be sampled during the puncture of the either needle types, and since these cells lack nuclei and are virtually dead, they have no potential to proliferate in wherever or whatever medium they may be transported to.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our previous studies and other recently published data [6,8,9], our study failed to demonstrate transportation of stratum basale cells, which, with their proliferative potential, could produce an epidermal tumour. Only stratum corneum cells ready to desquamate from the outermost layers of the skin could be sampled during the puncture of the either needle types, and since these cells lack nuclei and are virtually dead, they have no potential to proliferate in wherever or whatever medium they may be transported to.…”
Section: Discussionsupporting
confidence: 91%
“…In several published studies, potential for tissue transport by the spinal needles was investigated after inserting and removing various types of needles [3,6,9]. It was also shown that tissue coring occurs even if the stylet is in place and an introducer needle is used [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been advocated that the introducer should also have a stylet when initially placed through the skin, in order to avoid tissue coring within the introducer 2 . In a study of CSE interventions where the spinal needle was advanced through the epidural needle, epithelial cells were detected on the outer surface of the epidural needle in 33.3% of cases and in the internal washings of the epidural needle in 26.7% of cases 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Tunali and colleagues conducted a study to detect epithelial cell transfer in patients undergoing CSE interventions. Using a cytocentrifuge method, they analysed the CSF and spinal and epidural needle washings for epithelial cells and detected them in the CSF of 6.9% of the study patients 20 . Various other studies have reported an incidence of tissue coring of 15 to 80% after examining the tips and the shafts of the used spinal needles 1,2,18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation